LCP-tacrolimus in long-term kidney graft recipients: Dosing and adherence - Schill, Yvonne; Schiffer, Mario; Pape, Lars (Transplantation Reports, 2023)
Introduction: The new LCP-formulation of tacrolimus (Tac) has shown pharmacokinetic advantages in patients after liver transplantation that are associated with better adherence. The influence of prolonged release Tac on adherence, trough levels and dosing of Tac remains unclear. Methods: A prospective study was performed in 62 patients from two centers, who were switched to LCP-Tac after kidney transplantation, to assess adherence as defined by the Tac trough level coefficient of variation (CoV) (primary endpoint) and BAASIS© Score, as well as kidney function, Tac trough level and tacrolimus dose. Results: BAASIS© Score and Tac trough level CoV demonstrated good adherence over the study period, with no difference between the study timepoints (0.26 ± 0.16 at study start and 0.26 ± 0.11 at study end, p = 0.976, paired t-test). Graft function and Tac trough levels remained stable, and Tac dose could be reduced. Conclusions: A switch to LCP-Tac is feasible and leads to stable adherence, graft function and Tac trough levels, in combination with lower Tac doses.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Adherence; Coefficient of variation; Kidney transplantation; LCP; Tacrolimus; Trough level